Sagittal Plane Corrections around the Knee - Dejour, David; La Barbera, Giuseppe; Pasqualotto, Stefano; Valoroso, Marco; Nover, Luca; Reynolds, Ryan; Saffarini, Mo (The Journal of Knee Surgery, 2017)
Stability of the knee joint depends on soft tissues integrity and bony balance in the frontal and sagittal planes during gait. Although frontal plane imbalance is a well-known knee pathology, commonly treated by high tibial osteotomy, sagittal plane imbalance is less common, with fewer and more challenging surgical treatment options. The purpose of this review is to describe the biomechanical effects of sagittal knee imbalances and to outline the indications, techniques, and outcomes of sagittal knee osteotomies. The article details the reference axes and methods to measure posterior tibial slope (PTS), the principal indicator of sagittal imbalance, and its influence on anteroposterior tibial translations and rotational stability of the joint. The authors also outline the roles of the anterior and posterior cruciate ligaments in maintaining sagittal balance, with focus on the associations between PTS and ligament deficiencies, as well as posterolateral corner injuries. Different techniques and indications of tibial osteotomy in the sagittal plane, both above and below the anterior tibial tubercle, are compared in terms of technical difficulty, clinical benefits, and complication rates. The authors conclude on the importance of understanding sagittal knee imbalance, particularly in cases of ligament deficiencies, where the deformity can be the primary cause for lesions. Surgeons must identify the underlying deformities associated with sagittal imbalance, which can be recognized on weight-bearing X-rays and magnetic resonance imaging scans. Different techniques of sagittal osteotomies offer effective treatments for certain indications and should be considered in selected cases for unstable knees with ligament lesions.
Keywords: posterior tibial slope; sagittal; instability; imbalance; tibial deflexion osteotomy; antirecurvatum osteotomy